2020
DOI: 10.1088/1674-1056/ab7da4
|View full text |Cite
|
Sign up to set email alerts
|

Exploring ferromagnetic half-metallic nature of Cs2NpBr6 via spin polarized density functional theory*

Abstract: By employing the spin resolved density functional theory, half-metallic character is investigated in Cs2NpBr6 having a K2PtCl6-type structure. The results precisely predict the half-metallic behavior of Cs2NpBr6. In spin-down state it presents an indirect band gap, while in spin-up channel it turns metallic. The structure optimization confirms the half-metallic nature in ferromagnetic configuration. The calculated magnetic moment is 3 μ B toward which the main contributor is the Np atom. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…It is found that the band gap of the Cr-doped sample is smaller (2.312 eV) than that of the pristine sample (2.664 eV), demonstrating that the Cr doping induced improved capability for carrying both electrons and ions. In addition, the band structure can be divided into two paired lines, which correspond to the ±1/2 spin quantum number (up and down for +1/2 and −1/2) . The two paired lines in Na 3 V 2 (PO 4 ) 3 are well overlapped, while in Na 3 V 1.5 Cr 0.5 (PO 4 ) 3 , some lines are not.…”
Section: Results and Discussionmentioning
confidence: 99%
“…It is found that the band gap of the Cr-doped sample is smaller (2.312 eV) than that of the pristine sample (2.664 eV), demonstrating that the Cr doping induced improved capability for carrying both electrons and ions. In addition, the band structure can be divided into two paired lines, which correspond to the ±1/2 spin quantum number (up and down for +1/2 and −1/2) . The two paired lines in Na 3 V 2 (PO 4 ) 3 are well overlapped, while in Na 3 V 1.5 Cr 0.5 (PO 4 ) 3 , some lines are not.…”
Section: Results and Discussionmentioning
confidence: 99%
“…12 The alterations in the ratio or replacement of constituent cations and anions in the basic structure of perovskites AMX 3 alter their optoelectronic and magneto electronic properties 13 by resultingA 2 MX 6, 12 AMX 3 14 and A 2 BMX 6 15 like compounds (where, A, B and M are cations, and X is anion). Among the resulting compounds, some are halfmetallic [16][17][18][19][20][21][22][23][24] ferromagnetic having excellent physical properties. These have 100% spin polarization at Fermi level, as; they are metallic in one spin state and insulating or semiconducting in other spin state.…”
Section: Introductionmentioning
confidence: 99%
“…Our results are consistent with previous results, where the compounds of similar structures were found to be ferromagnetic. [ 27–29 ] We, therefore, consider Config‐II (ferromagnetic state) of these compounds for further calculations.…”
Section: Resultsmentioning
confidence: 99%
“…[ 37 ] If a compound is formed in a chemical reaction with release of energy (exothermic reaction), then it will be stable in the resulting phase. Theoretically, Δ H f can be calculated for the A 2 BX 6 compound by the following relation [ 29 ] normalΔHf=ETotal()A2BX62EAEB6Ex where E Total ( A 2 BX 6 ) and E A , E B E x are ground‐state energies of compound A 2 BX 6 and A , B , and X atoms, respectively. The calculated values of Δ H f for Rb 2 TaCl 6 and Rb 2 TaBr 6 are −30.014 and −24.455 eV, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation